Ultra‐low power consumption flexible sensing electronics by dendritic bilayer MoS2 - Lei Luo; Jiuwei Gao; Lu Zheng; Lei Li; Weiwei Li; Manzhang Xu; Hanjun Jiang; Yue Li; Hao Wu; Hongjia Ji; Xuan Dong; Ruoqing Zhao; et al. (InfoMat, 2024)
Abstract Two‐dimensional transition metal dichalcogenides (2D TMDs) are promising as sensing materials for flexible electronics and wearable systems in artificial intelligence, tele‐medicine, and internet of things (IoT). Currently, the study of 2D TMDs‐based flexible strain sensors mainly focuses on improving the performance of sensitivity, response, detection resolution, cyclic stability, and so on. There are few reports on power consumption despite that it is of significant importance for wearable electronic systems. It is still challenging to effectively reduce the power consumption for prolonging the endurance of electronic systems. Herein, we propose a novel approach to realize ultra‐low power consumption strain sensors by reducing the contact resistance between metal electrodes and 2D MoS2. A dendritic bilayer MoS2 has been designed and synthesized by a modified CVD method. Large‐area edge contact has been introduced in the dendritic MoS2, resulting in decreased the contact resistance significantly. The contact resistance can be down to 5.4 kΩ μm, which is two orders of magnitude lower than the conventional MoS2 devices. We fabricate a flexible strain sensor, exhibiting superior sensitivity in detecting strains with high resolution (0.04%) and an ultra‐low power consumption (33.0 pW). This study paves the way for future wearable and flexible sensing electronics with high sensitivity and ultra‐low power consumption.